Restorative justice, reconciliation, and peacebuilding - Llewellyn, Jennifer J. 1972-; Philpott, Daniel 1967- (Studies in strategic peacebuilding., 2014)
All over the world the practice of peacebuilding is beset with common dilemmas: peace versus justice, religious versus secular approaches, individual versus structural justice, reconciliation versus retribution, and the harmonisation of the sheer multiplicity of practices involved in repairing past harms. Progress toward the resolution of these dilemmas requires far more than reforming institutions and practices.